2021
DOI: 10.1136/bcr-2021-242695
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid-like rash revealing hypereosinophilic syndrome

Abstract: Hypereosinophilic syndrome (HES) is a rare haematologic disorder characterised by unexplained, persistent eosinophilia with organ involvement. We report the case of a 74-year-old patient who presented with a pemphigoid-like bullous rash as the only manifestation of an HES. This report highlights the importance of the dermatological manifestations of this potentially life-threating condition that may initially present as a skin-limited disease. Bullous pemphigoid (BP) is a very common autoimmune blistering derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…BP is a very common blistering disorder that can be associated with HES (9). HES must be considered especially in patients with atypical response to corticosteroids with blood eosinophilia (9). Our patient presented first with limited bullous lesions that resolved with corticosteroid treatment, but later recurred with a more generalized aggressive course with no response for low dose of corticosteroids.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…BP is a very common blistering disorder that can be associated with HES (9). HES must be considered especially in patients with atypical response to corticosteroids with blood eosinophilia (9). Our patient presented first with limited bullous lesions that resolved with corticosteroid treatment, but later recurred with a more generalized aggressive course with no response for low dose of corticosteroids.…”
Section: Discussionmentioning
confidence: 78%
“…When the genetic test is positive the best treatment is imatinib, whereas when the test is negative corticosteroids is considered as a first line of treatment (8). This case report shows the important role of dermatologists in diagnosing every skin manifestation even when cutaneous lesions are limited because it can highlight a life-threatening condition (9). BP is a very common blistering disorder that can be associated with HES (9).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…8 This case report underscores the critical role of dermatologists in diagnosing every skin manifestation, even when cutaneous lesions are limited, because a lifethreatening condition may exist. 9 BP is a common blistering disorder that may be associated with HES. 9 HES must be considered in patients with atypical corticosteroids response and eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal and hepatic involvement were simultaneously observed, similar to the present case. Khallaayoune et al reported a patient with HES who presented with bullous pemphigoid-like rash ( 12 ). In our case, although the patient had a history of bullous pemphigoid, the skin rash that appeared at the time of the diagnosis of HES was considered to be different from bullous pemphigoid, based on the findings of the skin biopsy.…”
Section: Discussionmentioning
confidence: 99%